A 24-hour thermoelectric generator simultaneous using solar heat energy and space cold energy. (August 2020) - Xia, Zhilin; Zhang, Zhenfei; Meng, Zhenghua; Yu, Zhongquan
Highlights: We have demonstrated a TEG to use the solar energy during the daytime and use the sky cold at night. This thermoelectric generator has a simple structure and the used materials are easy to obtain. This thermoelectric generator works environment friendly without consuming the existing energy on earth. Abstract: Here we have demonstrated a thermoelectric generator (TEG) to use the solar energy during the daytime and use the sky cold at night in which only a layer of SiC film was used to simultaneously absorb solar energy and radiate heat energy to the sky. A test TEG contains two pairs of thermoelectric legs and creates average 14.61 mV voltage in the daytime and 1.99 mV voltage at night, respectively. This generator has the advantages of simple structure and regular materials. It is a renewable energy source that works environment friendly without consuming the existing energy on earth, and great potential for using in the place without power transmission.